Frightening Complex Visual Hallucinations in an Elderly Patient with Ophthalmological Pathology and Vascular Dementia - Francesca Hill; Matthew Spurr; Joseph Stratford (Case Reports in Psychiatry)
A lady in her 90s was referred to the Later Life Team (LLT) in a rural area of the United Kingdom with complex visual hallucinations (VH). She had significant ophthalmological pathology, including cataracts, a branch retinal vein occlusion, and vitreous haemorrhage. The hallucinations included seeing monkeys ripping the heads off of her cats and lions prowling the garden. The patient was distressed by the hallucinations and believed them to be real events. Her management involved low dose olanzapine and requesting that her ophthalmological surgery be expedited. The surgery resulted in a significant reduction in VH. A diagnosis of vascular dementia went on to be made following cognitive testing and imaging. The cognitive impairment may have contributed to the patient’s inability to identify her experiences as hallucinations and thus render her without insight. A review of the computed tomography (CT) scans performed prior to the patient’s presentation to our service confirmed significant vascular pathology including small vessel disease and lacunar infarcts. Cognitive testing confirmed a cognitive impairment which had gone unnoticed by her family. This case leads to an interesting discussion regarding diagnosis in complex VH in cases of significant ophthalmological pathology but a lack of insight. Various authors have proposed theories to explain VH; cortical release and the Perception and Attention Deficit (PAD) model are explored as possible explanations for the experiences of this patient.